Estimating the intra-urban wage premium for a metropolitan area in a developing country - Campos, Rodger Barros Antunes; Azzoni, Carlos Roberto (Estudos Econômicos (São Paulo), 2024)
We estimated the intra-urban wage premium and its attenuation with a balanced panel of workers in the metropolitan area of Sao Paulo, Brazil. There are few studies dealing with the agglomeration effects on wages in developing countries, especially focusing on a fine geographical scale, as we consider in this paper. We geocoded the employment data on a grid of 9,071 cells of 1 km² and compared wages in the adjoining cells. We use Geographically Weighted Regressions to determine the size of the rings based on the AIC minimization method. We use worker and firm observable characteristics and fixed effects of firm, worker, and cell to deal with the selection of firms and workers. The estimated intra-urban wage premium ranges from 0.8% and 1.1%, depending on the size of the cells (0.5, 1, 2, and 4 km2). The attenuation effect is observed but restricted to 3 km from the inner cell and is stronger for less educated workers.